TEACHERS’ ORGANIZATIONAL CITIZENSHIP BEHAVIOUR IN IMPLEMENTING DISTANCE LEARNING AT SMAN 1 CERME DURING THE COVID-19 PANDEMIC - Amelia Rahmah Safira; Sulikah Asmorowati; Falih Suaedi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The COVID-19 pandemic has impacted all aspects of people's lives, one of which is education. The implementation of education in the midst of the COVID-19 virus outbreak is carried out through distance learning. This study aims to describe the organizational citizenship behaviour and the factors behind the organizational citizenship behaviour of teachers in implementing distance learning at SMAN 1 Cerme during the COVID-19 pandemic. This research used qualitative with descriptive method type. Data was collected by direct observation, interviews with 21 informants, and through secondary data. The technique of determining the informant is carried out using a purposive technique by determining the key informant which develops into a snowball technique. The results of this study indicate that teachers at SMAN 1 Cerme have demonstrated organizational citizenship behaviour in the implementation of distance learning. This is shown from five dimensions, namely altruism, sportsmanship, courtesy, civic virtue, and conscientiousness. While the factors behind the teachers of SMAN 1 Cerme to carry out organizational citizenship behaviour in the implementation of distance learning during the COVID-19 pandemic were perceptions of organizational support, organizational culture and climate, job satisfaction and leadership.